Evaluation of Program on Basic Sciences Courses in Elementary School Teacher Education’s Singkawang - Murdani, Eka; Susbiyanto, Susbiyanto; Sukardi, Rendi Restiana; Vilmala, Berry Kurnia; Ridwan, Irwan Muhammad; Jajuri, Titiyaka Binti (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study is to evaluate the Basic Sciences courses by examining their effectiveness in developing 21st-century skills, particularly the 4Cs (critical thinking, communication, collaboration, and creativity). This evaluation aims to ensure that the courses not only measure knowledge but also assess essential competencies for future learning and work. Methodology: This study employed the CIPP (Context–Input–Process–Product) evaluation model. The evaluators developed and implemented a Project-Based Learning (PjBL) model integrated with 4C competencies, abbreviated as PjBL4C. Data were collected through lesson plan analysis, pre-tests and post-tests for content knowledge and 4Cs, and performance assessments of communication and collaboration skills. Student satisfaction was also measured using a structured questionnaire. Main Findings: The implementation of the PjBL4C model in Basic Sciences courses showed a significant improvement in students’ achievement and 4C competencies. The number of students reaching the standard level increased based on pre-test and post-test results. At the end of the course, the evaluation successfully identified the overall 4C profiles of students categorized into three levels: below, approaching, and at standard. Novelty/Originality of this study: This study introduces PjBL4C as an innovative instructional model that simultaneously develops and measures 4C skills in higher education. Additionally, the 4C assessment instrument was designed and aligned with the PjBL syntax, enabling accurate classification of students’ competencies across multiple skill domains.